Analisis Biaya Factory Overhead Dalam Kaitannya Dengan Penentuan Perilaku Biaya Menggunakan Metode High Low Dan Metode Scattergraph Studi Kasus pada CV. Jagor Jaya - Iriyadi, Iriyadi; Wijaya, Ferlin (Jurnal Ilmiah Ranggagading (JIR), 2008)
This research has a goal, that is to find out FOH Cost Analysis in connection with cost characteristic fixation by high low method and scattergraph method. By utilizing high low method and scattergraph method, it will be able to be separated fixed cost and variable cost. The outcome of this research shows that CV Jagor Jaya do not applicate FOH Cost based on cost characteristic by high low and scattergraph method. Whereas, by using the method mentioned above, it will make the company easier to find out cost increase or decrease in one year. Keywords: Factory overhead cost; High low and scattergraph method.